(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Data about maximum thermal tolerance in marine organisms are needed to prevent the extinction of species due to global warming. The aim of this study is determining the maximum lethal temperature of Haliotis squamata. In this study, H. squamata were placed in individual containers and exposed to 5 different levels of temperature (27°C, 28.5°C, 30°C, 31.5°C, and 33°C, n = 20). The temperature was raised 0.5°C per 12 hours starting from ambient conditions until target temperatures were reached. The mortality was monitored since animals moved to the individual containers. The results showed that the maximum thermal limit of H. squamata is 31.5°C and 33°C is the lethal temperature, the temperature level with the lowest survival rate (0.15). The IPCC predict that sea surface temperature will raise up to 4°C and monthly average sea surface temperature in Indonesia is around 26 – 31°C. That means in the next century average sea surface temperature could be more than the maximum thermal limit of H. squamata. Thus, early conservation is needed to protect H. squamata.